Entry on the Brazilian renewable power market: a case study - La Claviere, Charles Daniel Hely Marie (2016)
International climate conferences as well as growing awareness over sustainability issues have shed light on the key role renewable energies would play in the energy transition. As opposed to fossil fuels, they can be regenerated on a short period of time and therefore are expected to be part of the solution to limit global warming. For decades, Brazil has had a strong hydroelectric sector, but it is now also a leader in all other alternative energy sources such as wind power, biomass or solar energy. These industries are promised a thriving future, thanks to the country’s natural potential as well as a supportive legislation, and are attracting many local and international players. This study aims to fill a void in literature analyzing the example of a foreign firm entering on the Brazilian renewable power market. Relying on literature as a conceptual background, a single case study has been conducted to outline all the aspects of the entry process. In this development, causal relationships between strategic orientations and the evolution of the business have been identified. This research brings a contribution to the academic discussions over entry dynamics in the renewable power industry through evidences from the Brazilian market.